Gemba kaizen a commonsense low-cost approach to management - Imai, Masaaki (McGraw-Hill, 2001)
When it comes to making your business more profitable and successful, don't look to re-engineering for answers. A better way is to apply the concept of kaizen, which mean making simple, common-sense improvements and refinements to critical business processes.The result: greater productivity, quality, and profits achieved with minimal cost, time, and effort invested. In this book, you discover how to maximize the results of kaizen by applying it to gemba--business processes involved in the manufacture of products and the rendering of services--the areas of your business where, as the author puts it, the "real action" takes place.